The Collateral Impacts of Pandemic - Ceva Wicaksono Pitoyo (Interna Publishing, 2020)
A pandemic that covers the whole world occurs relatively in every 100 years. Thus, it can be said that no expert has ever experienced directly dealing with a global pandemic. In the absence of people who are truly experts who know the problems and impacts of a global pandemic, various studies need to be carried out extensively between fields and across regions in the world. Likewise, the results of the study need to be recorded permanently so that it can still be useful over a long period of time, preferably for more than a hundred years. Studies of the short-term and long-term impacts of the pandemic on things other than mortality are calling us to be worked upon. It is the time for us to be concerned with the risk assessment of benefits before a decision is taken and its openly scientific reporting. It is necessary to develop strategies to mitigate or avoid dire consequences of a policy. Until now, studies of health policy on the vulnerable group seem to be minimally done. It would be wise to encourage more studies to groups that are vulnerable to the impact of a policy. The collateral impacts of the pandemic do not only affect the health services on diseases other than Covid-19, but also includes the collateral impact of humanitarian threats in other fields. Management of a global pandemic needs to be carried out comprehensively, both in handling the disease, support for and access to other diseases, as well as collaboration and socioeconomic policies that maintain the pillars of humanity. Lessons must be taken by humans in order to defend their race in the future, including pandemics that occur repeatedly over a span that is longer than the age of three generations.